Nuclear gene mutations as the cause of mitochondrial complex III deficiency - Fernández-Vizarra, Erika; Zeviani, Massimo (Frontiers in Genetics, 2015)
Complex III (CIII) deficiency is one of the least common oxidative phosphorylation defects associated to mitochondrial disease. CIII constitutes the center of the mitochondrial respiratory chain, as well as a crossroad for several other metabolic pathways. For more than ten years, of all the potential candidate genes encoding structural subunits and assembly factors, only three were known to be associated to CIII defects in human pathology. Thus, leaving many of these cases unresolved. These first identified genes were MT-CYB, the only CIII subunit encoded in the mitochondrial DNA; BCS1L, encoding an assembly factor, and UQCRB, a nuclear-encoded structural subunit. Nowadays, thanks to the fast progress that has taken place in the last three-four years, pathological changes in seven more genes are known to be associated to these conditions. This review will focus on the strategies that have permitted the latest discovery of mutations in factors that are necessary for a correct CIII assembly and activity, in relation with their function. In addition, new data further establishing the molecular role of LYRM7/MZM1L as a chaperone involved in CIII biogenesis are provided.